Comparative risk of cardiac arrhythmias associated with acetylcholinesterase inhibitor use - Huang, Yichang (University of Waterloo, 2021)
Background: Acquired long-QT syndrome (ALQTS) and its associated condition, torsades de pointes (TdP – a malignant cardiac arrhythmia), are associated with the use of certain medications. Case reports and pharmacodynamic studies suggest donepezil, one of the three acetylcholinesterase inhibitors (AChEIs) used in the treatment of Alzheimer’s Disease (AD) and related dementias, may be associated with a greater risk of ALQTS and malignant arrhythmias. Only a limited number of studies have generated relevant information, and no population-based epidemiologic studies have directly examined comparative risk between AChEIs. Methods: Using Canadian hospitalization and prescription medication administrative databases – the Discharge Abstract Database (DAD) and National Prescription Drug Utilization Information System (NPDUIS) respectively – I included individuals in seven jurisdictions (British Columbia, Alberta, Saskatchewan, Manitoba, Ontario, Prince Edward Island, Newfoundland and Labrador) between April 1st 2011 and January 31st 2019. Included adults were aged 66 and over, and either initiated the use of donepezil, galantamine, oral rivastigmine, or transdermal rivastigmine (defined as no previous dispensation of AChEI recorded in NPDUIS in 365 days prior). The outcome of a hospitalization for malignant arrhythmia was identified by ICD-10-CA codes I47.2 and I49.00. The hospitalization date set as the 15th of the month in primary analysis (with adjustment to first or end of month in sensitivity analyses) and a multivariable Cox regression model was fitted to estimate the hazard of a hospitalization for malignant arrhythmia, dependent upon AChEI use. The primary analysis assessed the time to hospitalization for malignant arrhythmia using the primary DAD diagnostic field and a maximum available follow-up of eight years. In secondary analyses, I included malignant arrhythmia codes from any diagnostic field and limited follow-up to 365 days. Variables adjusted for include demographic covariates and comorbidities ...